Video WhatsApp (Vidsapp) on Vitamin C and Selenium: An Innovation to Enhance Knowledge and Control Blood Glucose in Diabetes Mellitus Patients - Jefa Chori Alsiya; Fifi Luthfiyah; Fitria Dhenok Palupi (Poltekkes Kemenkes Semarang, 2026)
Background: Diabetes mellitus (DM) is a chronic disease caused by insulin resistance and pancreatic beta-cell dysfunction. The prevalence of DM among individuals aged ≥15 years in Indonesia increased from 6.9% in 2013 to 8.5% in 2018. DM management includes educational, nutritional, physical activity, and pharmacological interventions. Vidsapp, a WhatsApp-based video education medium, is expected to improve patients’ understanding of vitamin C and selenium in controlling blood glucose levels. Objective: To analyze the effect of Vidsapp-based nutrition education on knowledge, vitamin C and selenium intake, and fasting blood glucose (FBG) levels in patients with type 2 DM. Methods: This study used a pre-experimental one-group pretest-posttest design involving 31 respondents selected through purposive sampling at Lawang Public Health Center. Results: The mean knowledge score increased by 27.09, vitamin C and selenium intake increased by 4.29 mg and 1.9 µg/day, respectively, and FBG levels decreased by 15.13 mg/dL. Significant differences were found in knowledge (p=0.000) and FBG levels (p=0.025), while no significant differences were observed in vitamin C intake (p=0.564) and selenium intake (p=0.544). Conclusion: Vidsapp-based nutrition education is effective in improving knowledge and reducing FBG levels in patients with type 2 DM but does not significantly affect vitamin C and selenium intake.